Extrapolation of carcinogenic risk from animal experiments in man. - Ehrenberg, L (1978)
When estimating the absolute risk of cancer, the shape of the dose--response curve in the region of doses where actual exposure of man occurs is of crucial importance. This shape is equally important for the determination of relative risks, as in the comparison of risks from alternative energy sources. Experimental and epidemiological studies are, for various reasons, unable to give sufficiently exact information concerning the dose response in the low dose region. Therefore, the discussion concerning dose--response relationships also has to consider biologically reasonable mechanisms for the origin of tumors.